The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/anie.200352859
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Generating Naked‐Metal Clusters for Gas‐Phase Reactivity Studies by FTICR–MS

Abstract: Cluster reactivity in the gas phase has been probed extensively with clusters generated by using a variety of custombuilt sources. These include pulsed-laser vaporisation, continuous-operation ovens, fast-atom and secondary-ion sputtering, dc discharge, and pulsed-arc cluster-ion sources.[1] All generate an assortment of clusters of different nuclearities, and MS n techniques make selection of a particular sized cluster relatively straightforward. Both homo-and heteronuclear clusters are known.[2] All of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Electrospray ionization (ESI [139,140]) brought very powerful technique for gas-phase mechanistic studies [115,[141][142][143]. Using hard ionization conditions (large collision energies of the electrospray droplets with the drying gas [144]), highly reactive species can be generated and consequently used as models for catalysis.…”
Section: More Complex Systems As Models For Chemical Reactivitymentioning
confidence: 99%
“…Electrospray ionization (ESI [139,140]) brought very powerful technique for gas-phase mechanistic studies [115,[141][142][143]. Using hard ionization conditions (large collision energies of the electrospray droplets with the drying gas [144]), highly reactive species can be generated and consequently used as models for catalysis.…”
Section: More Complex Systems As Models For Chemical Reactivitymentioning
confidence: 99%
“…However, studies by McIndoe et al [42] demonstrated that chemically synthesized atomically precise metal clusters could be used as precursors of naked metal clusters. Similarly, reactivity studies of partially ligated gas-phase metal clusters can be performed using chemically made, atomically precise clusters as a source, and easily installed and inexpensive modifications to electrospray ionization mass spectrometers [43].…”
Section: Size Effects -Setting the Scenementioning
confidence: 99%
“…Two Ru III complexes are currently undergoing clinical trials as anti-cancer agents, and Ru II arene complexes have shown promising activity in model cancer systems [1]. Ruthenium has seven isotopes, making the mass isotopic pattern of ion peaks of ruthenium-containing compounds characteristic, yet complicated [2][3][4][5][6]. In our previous work [2,3,[7][8][9], mass spectra acquired by electrospray ionization (ESI-MS) equipped with a quadrupole mass analyzer allowed unambiguous assignment of singly charged ion peaks of mononuclear ruthenium arene complexes as well as their adducts with amino acids, peptides, and DNA.…”
mentioning
confidence: 99%